The impact of strategic agility on organisational performance moderated by digital transformation in firms within the city of Johannesburg South Africa - Chiba, Manoj (University of Pretoria, 2026)
Mini Dissertation (MPhil (Corporate Strategy))--University of Pretoria, 2025.